Quadriceps muscle thickness changes in patients with aneurysmal subarachnoid hemorrhage during the acute phase. Issue 3 (3rd April 2018) - Nozoe, Masafumi; Kanai, Masashi; Kubo, Hiroki; Kobayashi, Miki; Yamamoto, Miho; Shimada, Shinichi; Mase, Kyoshi
Abstract: Background: Aneurysmal subarachnoid hemorrhage (aSAH) is a life-threatening condition that often leads to severe disability in relatively young and healthy people. This disability is physical in many aSAH survivors, so muscle dysfunction may be an important factor in the functional level of these patients. Thus, measuring muscle thickness represents a suitable method for determining muscle function in patients with acute aSAH, because the disordered consciousness often experienced during the acute phase causes active movement to be difficult for these patients. Objectives: We investigated changes in quadriceps muscle thickness in patients with aneurysmal subarachnoid hemorrhage to determine whether muscle dysfunction during the acute phase relates to (or predicts) the outcome of aSAH. Methods: Seventeen patients with aSAH (mean age = 66 ± 11, men/women = 4/13) were enrolled, and their quadriceps muscle thickness measured ultrasonographically upon admission and again 2 weeks later. Results: Quadriceps muscle thickness significantly decreased from admission (mean = 3.00 ± 0.72 cm) to the second measurement (2.67 ± 0.74 cm, p  = 0.001). The relative differences in quadriceps muscle thickness were correlated with the Hunt and Hess grade ( r  = −0.72, p  = 0.001) and the modified Rankin Scale score at 90 days ( r  = −0.78, p  = 0.0002). Conclusions: Our results indicate that quadriceps muscle thickness decreases in patients with acute aneurysmal subarachnoid hemorrhage, particularly in patients with poor Hunt and Hess grade or marked disability.